2003
DOI: 10.1038/sj.bjc.6600775
|View full text |Cite
|
Sign up to set email alerts
|

Vegetables and fruit intake and cancer mortality in the Hiroshima/Nagasaki Life Span Study

Abstract: The association between green-yellow vegetables and fruit consumption and risk of cancer death was investigated in a prospective study of 38 540 men and women who were atomic-bomb survivors in Hiroshima and Nagasaki, Japan. Study participants completed a dietary questionnaire in 1980 -1981 and were followed-up for cancer deaths until March 1998, during which time 3136 cancer deaths were identified. Daily or almost daily fruit consumption was associated with a significant 12% reduction in total cancer mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 51 publications
6
118
0
2
Order By: Relevance
“…In contrast, reviews by Gandini et al 25 and Riboli & Norat 26 showed a protective relationship for vegetables, but not for fruits. Furthermore, other studies have shown no association for either group 27,28 .…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, reviews by Gandini et al 25 and Riboli & Norat 26 showed a protective relationship for vegetables, but not for fruits. Furthermore, other studies have shown no association for either group 27,28 .…”
Section: Discussionmentioning
confidence: 88%
“…The results of our study are consistent with those of some previous studies. 9,10,12 A prospective cohort study conducted in Japan reported that daily green-yellow vegetable intake provided an approximately 8% reduction in risk for total cancer mortality and a 25% reduction for liver cancer mortality; 9 a case-control study in Italy also showed a significant inverse association for subjects with a high frequency of vegetable consumption; 10 a cohort study of Taiwanese men showed a 4.7-fold increased risk of hepatocellular carcinoma in those who had a weekly vegetable consumption frequency of less than 6 meals a week, compared with those who had a frequency of 6 or more meals. This association was observed in HBsAg carriers but not in noncarriers; 12 while another casecontrol study in Greece found no evidence that vegetable intake reduces the risk of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to liver cancer, however, we have identified only a few studies, which examined the association between vegetable consumption and liver cancer, and the results of these were inconsistent. [9][10][11][12] To contribute to clarifying this relationship, we conducted this study to investigate the association between vegetable consumption and liver cancer mortality, based on a population-based prospective cohort study in Japan.…”
mentioning
confidence: 99%
“…A recent metaanalysis of case-control studies estimated that high fruit and vegetable consumption decreased the risk of pancreatic cancer by 28% and 20%, respectively (6). However, most prospective cohort studies have not shown a protective influence for fruits and vegetables on pancreatic cancer (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%